Colchicine at a Low Dose Reduces Liver Inflammation in a Model of Immune-Mediated Hepatitis - Azmanov, Henny; Keidar-Haran, Tal; Kenig, Ariel; Kessler, Asa; Kolben, Yotam; Zangen, Sarah Weksler-; Ilan., Yaron (Archives of Clinical and Biomedical Research, 2023)
Introduction: Colchicine is an anti-inflammatory drug with a limited effect on the systemic immune system and unwanted side effects. Chronobiology and variability-based dosing regimens may improve the efficacy of chronic drugs. This study investigates the effect of colchicine's low-dose and variability-based dosing regimens on Concanavalin-A (ConA)-induced hepatitis in mice. Methods: ConA was injected intravenously into mice to induce immune hepatitis, a higher dose was used to simulate acute hepatitis, and repeated lower dosages simulated a chronic liver disease. Low-dose colchicine was orally administered to mice via gavage. The chronic model included a subgroup who received colchicine using a variability-based regimen. Studies were terminated after 16 hours and 11 days in the acute and chronic groups, respectively. Mice were tested for AST and ALT serum levels and liver pathology. Results: Low-dose colchicine improved the well-being of mice in the chronic injury model, significantly decreased the ALT serum levels vs. vehicle-treated mice, and reduced necrosis and lymphocyte infiltration in the liver. Using a variability-based dosing regimen altered the drug's therapeutic effect. Acute colchicine treatment improved the general wellbeing of mice and showed a trend for a decrease in liver enzymes. Conclusions: This study suggests that low doses of oral colchicine reduce liver injury in chronic liver damage cases. It was demonstrated by weight gain, overall well-being improvement, and healthier liver tissue appearance. These findings support the idea of testing oral low-dose colchicine in conditions that involve immune system dysfunction.